Long noncoding RNA matrilineal expression gene 3 inhibits hepatocellular carcinoma progression by targeting microRNA-5195-3p and regulating the expression of forkhead box O1. Issue 2 (20th December 2021) - Li, Minan; Liao, Hong; Wu, Jian; Chen, Bin; Pang, Runhua; Huang, Junhai; Zhu, Yaqing
ABSTRACT: We investigated the effect of the long noncoding RNA (lncRNA) maternally expressed gene 3 (MEG3) on hepatocellular carcinoma (HCC) tumorigenesis and progression by targeting miR-5195-3p and transcription factor forkhead box O1 (FOXO1) to identify a novel target for HCC treatment. HCC clinical samples were collected, and cell counting kit-8 (CCK-8), and transwell migration and invasion assays were performed. Furthermore, interaction was detected via double luciferase reporter and RNA pull-down assays. MEG3, miR-5195-3p, and FOXO1 expression was determined by quantitative real-time polymerase chain reaction (RT-qPCR) and Western blotting. Xenograft tumor models were established to investigate the effect of MEG3 in vivo . Compared with normal tissues, MEG3 expression was significantly downregulated in HCC tissues. MEG3 overexpression inhibited the viability and migration of HCC cells. Double luciferase reporter and RNA pull-down assays confirmed the binding between MEG3 and miR-5195-3p as well as between miR-5195-3p and FOXO1. RT-qPCR and Western blotting results showed that MEG3 inhibited the expression of miR-5195-3p and promoted that of FOXO1. Additionally, MEG3 overexpression inhibited HCC tumorigenesis and progression in xenograft tumor models while depletion of MEG3 exerted the opposite way. Therefore, the lncRNA MEG3 inhibits HCC tumorigenesis and progression through the miR-5195-3p/FOXO1 signaling axis.